"Slowly. slowly. slowly." said the sloth. - Carle, Eric; Goodall, Jane, 1934- (New York : Philomel Books, 2002)
Challenged by the other jungle animals for its seemingly lazy ways, a sloth living in a tree explains the many adventures of his slow and peaceful existence.
SJ 09/02, KK 08/01/02, PW 07/01/02
0205
Keywords: Oversize books -- Specimens -- Juvenile fiction; Sloths -- Juvenile fiction; Jungle animals -- Juvenile fiction; Animals -- Juvenile fiction